2018
DOI: 10.1177/0734242x17751847
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on electrical surface modification of waste to energy ash for possible use as an electrode material in microbial fuel cells

Abstract: With the world population expected to reach 8.5 billion by 2030, demand for access to electricity and clean water will grow at unprecedented rates. Municipal solid waste combusted at waste to energy (WtE) facilities decreases waste volume and recovers energy, but yields ash as a byproduct, the beneficial uses of which are actively being investigated. Ash is intrinsically hydrophobic, highly oxidized, and exhibits high melting points and low conductivities. The research presented here explores the potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…There is also an attempt to create a binding geopolymer that will replace classic cement [18,19], as well as the production of more durable ceramic building materials (modern bricks) [16,20]. In addition to the above traditional applications, intense research has been reported in recent years on the use of FA in the fuel cell industry to produce more efficient electrodes [21] and polymeric electrolytic membranes [22]. Also, the simultaneous utilization of FA and sewage sludge has led to the construction of high-performance anodes for MFCs [23], while research effort is also expanding in the field of ion-lithium battery performance optimization, by adding a film of FA to the cathode [24].…”
Section: Introductionmentioning
confidence: 99%
“…There is also an attempt to create a binding geopolymer that will replace classic cement [18,19], as well as the production of more durable ceramic building materials (modern bricks) [16,20]. In addition to the above traditional applications, intense research has been reported in recent years on the use of FA in the fuel cell industry to produce more efficient electrodes [21] and polymeric electrolytic membranes [22]. Also, the simultaneous utilization of FA and sewage sludge has led to the construction of high-performance anodes for MFCs [23], while research effort is also expanding in the field of ion-lithium battery performance optimization, by adding a film of FA to the cathode [24].…”
Section: Introductionmentioning
confidence: 99%